2021
DOI: 10.2196/18764
|View full text |Cite
|
Sign up to set email alerts
|

User Perspectives on Barriers and Facilitators to the Implementation of Electronic Health Records in Behavioral Hospitals: Qualitative Study

Abstract: Background Despite the rapid adoption of electronic health records (EHRs) resulting from the reimbursement program of the US government, EHR adoption in behavioral hospitals is still slow, and there remains a lack of evidence regarding barriers and facilitators to the implementation of mental health care EHRs. Objective The aim of this study is to analyze the experience of mental health professionals to explore the perceived barriers, facilitators, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 24 publications
(29 reference statements)
1
37
0
3
Order By: Relevance
“…Furthermore, lower digital competence (ie, computer proficiency) has been found to be a barrier to successful implementation of electronic health records in psychiatric hospitals [ 11 ]. This would imply that Swiss psychiatric hospitals have a good precondition for the successful implementation of digital technologies, as the digital competence of health professionals was rated high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, lower digital competence (ie, computer proficiency) has been found to be a barrier to successful implementation of electronic health records in psychiatric hospitals [ 11 ]. This would imply that Swiss psychiatric hospitals have a good precondition for the successful implementation of digital technologies, as the digital competence of health professionals was rated high.…”
Section: Discussionmentioning
confidence: 99%
“…The demands for digital competences and associated changes in the role of health professionals also require a change in the perception of and attitude toward digital resources in everyday work [ 11 ]. Consequently, this transformation may have a stress-inducing effect on health professionals, especially because psychiatric health professionals tend to be hesitant regarding new technologies because of the expected deleterious effects on the relationship between health professionals and patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies took place in the United States (27/40, 68%) [ 80 - 83 , 85 - 90 , 92 - 98 , 101 , 102 , 104 , 106 , 110 - 113 , 115 , 116 ], followed by the United Kingdom (8/40, 20%) [ 78 , 84 , 99 , 100 , 105 , 107 , 108 , 117 ]. Canada (2/40, 5%) [ 79 , 114 ], France (1/40, 3%) [ 103 ], Brazil (1/40, 3%), and Ireland (1/40, 3%) [ 91 ] were also represented in the included studies.…”
Section: Methodsmentioning
confidence: 99%
“…We first identified studies that expected to report the details of the EHR in their methods sections, such as the evaluations of specific EHRs (28/40, 70%) [ 78 , 79 , 81 - 84 , 87 - 89 , 91 , 92 , 95 , 99 - 111 , 114 , 115 , 117 ]. Of these 28 studies, 16 (57%) either named the EHR or provided details as to whether it was custom built or off the shelf [ 78 , 79 , 83 , 84 , 89 , 95 , 99 - 102 , 105 - 108 , 110 , 117 ]. One of the studies pointed to other publications in which the details of the EHR were reported [ 103 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation